Association between depressive symptoms and balance disorders in older adults living in 12 high Andean communities - Maite T. Alanya-Pineda; Ivonne A. Bravo-Alcántara; Ana L. Alcantara-Diaz; Leslie Salazar-Talla; Diego Urrunaga-Pastor; Fernando M. Runzer-Colmenares; José F. Parodi (PLoS ONE, 2026)
Background The prevalence of depressive symptoms and balance disorders may be higher in high-altitude Andean regions due to chronic hypoxia, neurochemical alterations, and limited access to health services. Since both conditions can coexist and contribute to functional decline and falls, their association is relevant. We aimed to estimate the association between depressive symptoms and balance disorders in older adults living in 12 high Andean communities. Methods We carried out a secondary analysis of data from a cross-sectional analytical study in older adults residing in 12 Peruvian high Andean communities during the period 2013–2020. The exposure variable was depressive symptoms (defined as a score greater than or equal to two on the five-item geriatric depression scale), while the outcome variable was balance disorders (defined by a functional reach test less than or equal to 20.32 cm). We constructed generalized linear models from Poisson family with link log and robust variances. We estimated crude (cPR) and adjusted (aPR) prevalence ratios with their respective 95% confidence intervals (95%CI). Results We analyzed 417 older adults; 61.1% (n = 255) were women, with a mean age of 73.2 ± 6.9 years. Additionally, 52.8% (n = 220) presented depressive symptoms, while 48.9% (n = 204) presented balance disorders. In the adjusted regression model, depressive symptoms were associated with a higher prevalence of balance disorders in older adults (aPR = 1.66; 95%CI: 1.28–2.15; p < 0.001). Conclusions Depressive symptoms were associated with a higher prevalence of balance disorders in older adults residing in the 12 high Andean communities. Future epidemiological studies with a larger sample size are needed to evaluate depressive symptoms and balance disorders to develop early screening programs in older adults to improve their quality of life and access to primary health care.